THE STUDY OF FOLIC ACID AND VITAMIN B12 LEVELS IN ANAEMIA IN PREGNANCY - YOGENDER P; BALRAM SINGH THAKUR; RANGASWAMY R; SREEKANTHA (International Journal of Pharma and Bio Sciences, 2014)
In developing countries the prevalence of anaemia among pregnant women averages 56%, ranging between 35 to 100% among different regions of the world. Various studies from different regions of the country (India) have reported the prevalence of anaemia to be between 33 and 100%.In India, anaemia is the second most common cause of maternal deaths, accounting for 20% of total maternal deaths. Anaemia affects mainly the women in child bearing age group, young children and adolescent girls. Association of anaemia with adverse maternal outcome such as puerperal sepsis, ante-partum haemorrhage, post-partum haemorrhage and maternal mortality is no longer a debatable subject. Folic acid and vitamin B12 are essential in the synthesis of nucleoprotein, particularly of erythropoietic cells. Hence this study is taken to study the serum levels of Folic acid and vitamin B12 in pregnant ladies and correlate with seviarity of anaemia.